PERANAN PENDlDlKAN KEWIRAUSAHAAN DALAM MENUMBUH KEMBANGKAN KEMANDIRIAN MAHASISWA FKIP DALAM ERA PERSAINGAN BEBAS - Isjoni Isjoni (LPMPP Universitas Negeri Yogyakarta, 2003)
The efforts to develop human resources through educationalinstitutions must result satisfactorily. Therefore, Indonesia tries'toexpand educational programs through two channels: formal andinformal education.Nowadays, the Departmentof National Education is trying todevelop educational programs that make a link and match betweengraduates and job opportunities.So far, the system of education hasproduced increasingly more work forcesso that not all of them canbe accommodated by the existing jobs in industries or governmentoffices. Next, they generally compete to become civil servants whilethe vacancies are very limited. Moreover, school and universitygraduates tendto be cognitively oriented rather than academicallywork skilledso that they do not meet working needs. In order tomeet these needs oneof the efforts which can be carried out isthrough entrepreneur education.Entrepreneur educationis a kind of education intended forschool or university students and expectedto generate entrepreneursin all levels. Theyare expected to be able to begin, develop, andstimulate their entrepreneur ability by using their own competencieswithout dependingtoo much on others' assistance. Therefore,entrepreneur education refers moreto the efforts to increase humanresources and new job opportunities and finally it can givecontribution to the growthofthe national economy